THE LEVEL OF TACTICAL SKILLS AMONG YOUNG FOOTBALL PLAYERS - Abbas, Mohammed Ashour (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. The tactical aspects in sports are considered essential for improving the performance of players and raising the level of their abilities, as tactical thinking is one of the basic elements in competitive sports performance, as it plays an important role in making decisions and achieving goals. In this context, Al-Jabali pointed out the importance of tactical thinking in improving the performance of athletes and achieving goals. Objectives. The research aims to identify the level of tactical skills among young players in the Electrical Industries and Civil Defense Sports Club, as well as to identify the differences between them in terms of these skills. Method. The researcher used the descriptive analytical method in this research, as he applied a measure of tactical skills, which is the Everlink scale consisting of (21) a statement divided into four areas. The researcher chose the research community intentionally, namely the young players in the Electrical Industries and Civil Defense Club. The research sample was chosen randomly from within this community, numbering (28) players, and after the researcher completed his procedures. Results. The results of the current research showed that the level of tactical skills among the players of the Electrical Industries Club and the players of the Civil Defense Club reached a high degree through the scale, the level of tactical skills among the players of the two clubs was approximately the same level. Conclusion. The researcher came out with several recommendations: Coaches pay attention to the tactical aspect of players, especially the junior and youth categories, and emphasis on club administrations selecting coaches with a high degree of psychological and general culture in the players’ intellectual affairs.